TRANSAKSI E-COMMERCE BERBASIS MARKET PLACE: ANTARA AKAD SALAM DAN GHARAR PERSPEKTIF FIQIH MADZHAB SYAFI`I) - Dani El Qori (Institut Keislaman Abdullah Faqih Gresik, 2020)
Technological developments have an impact on changes in habits and lifestyles in all walks of life, including in the line of economic transactions. Buying and selling transactions that were initially carried out face-to-face between sellers and buyers have shifted to a new style of online trading transactions via the internet or commonly known as e-commerce. This transaction model offers the convenience of transactions that are not bound by time and place. However, behind this convenience, problems arise in the form of widespread fraud and unclear object transactions. This problem is responded to by the existence of a market place service that offers security in transactions. In the fiqh literature, this e-commerce transaction is close to the salam contract. In this paper, we will discuss the existence of gharar and the application of the salam contract in e-commerce transactions based on market place. The author uses the salam contract theory in the perspective of the Shafi`i school of thought.Kata Kunci : e-commerce, market place , gharar, salam.